Transient performance during start-up of a two-phase anaerobic digestion process demonstration unit treating carbohydrate-rich waste with biochar addition. (31st May 2019) - Sunyoto, Nimas M.S.; Sugiarto, Yusron; Zhu, Mingming; Zhang, Dongke
Abstract: The paper reports an experimental investigation into the transient performance during the start-up of a pilot-scale two-phase anaerobic digestion (TPAD) process demonstration unit (PDU) treating food waste with biochar addition. Hydrogen (H2 ) was produced in the first phase (R1) and methane (CH4 ) was produced in the second phase (R2). A fed-batch operation strategy was applied to the start-up of both phases, followed by semi-continuous operation. Production rates and yields of H2 and CH4 and volatile fatty acids (VFA) were measured while the pH and temperature were monitored throughout the process. Fed-batch operation allowed microbe enrichment and gradual VFA production in both phases, which was observed to be efficient in starting up the TPAD PDU. Under semi-continuous operation, R1 produced biogas with composition up to 49% of H2 and at a yield of 46 L H2 .kg −1 VS. CH4 composition and yield reached up to 59% and 301 L CH4 .kg −1 VS in the R2. Highlights: Start-up of a demonstration scale of TPAD treating food waste was conducted. Successful start-up was achieved with fed-batch followed by semicontinuous strategy. Stable H2 production with 46 L kg −1  VS was obtained in the first phase of TPAD. Stable CH4 production with 300 L kg −1  VS was attained in the second phase of TPAD.